2023
DOI: 10.1001/jamacardio.2022.5211
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rurality With Risk of Heart Failure

Abstract: ImportanceRural populations experience an increased burden of heart failure (HF) mortality compared with urban populations. Whether HF incidence is greater among rural individuals is less known. Additionally, the intersection between racial and rural health inequities is understudied.ObjectiveTo determine whether rurality is associated with increased risk of HF, independent of cardiovascular (CV) disease and socioeconomic status (SES), and whether rurality-associated HF risk varies by race and sex.Design, Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Compared with their urban counterparts, southern rural residents had a 19% greater risk of incident HF. 28 This study also reported important race- and sex-related differences in HF risk; the greatest rurality-associated risk of incident HF was in Black men (34%), White women (22%), and Black women (18%), while White men had a 3% lower risk than the overall group. The approach of RURAL to incorporating echocardiography into the baseline examination provides a paradigm-shifting approach to assess the burden of subclinical and clinical cardiac dysfunctions in selected rural communities that have hitherto had limited access to advanced cardiac imaging technology that is vital for CVD prevention.…”
Section: Unmet Needs: Imaging and Detecting Subclinical Coronary Athe...supporting
confidence: 50%
See 2 more Smart Citations
“…Compared with their urban counterparts, southern rural residents had a 19% greater risk of incident HF. 28 This study also reported important race- and sex-related differences in HF risk; the greatest rurality-associated risk of incident HF was in Black men (34%), White women (22%), and Black women (18%), while White men had a 3% lower risk than the overall group. The approach of RURAL to incorporating echocardiography into the baseline examination provides a paradigm-shifting approach to assess the burden of subclinical and clinical cardiac dysfunctions in selected rural communities that have hitherto had limited access to advanced cardiac imaging technology that is vital for CVD prevention.…”
Section: Unmet Needs: Imaging and Detecting Subclinical Coronary Athe...supporting
confidence: 50%
“…The approach of RURAL to incorporating echocardiography into the baseline examination provides a paradigm-shifting approach to assess the burden of subclinical and clinical cardiac dysfunctions in selected rural communities that have hitherto had limited access to advanced cardiac imaging technology that is vital for CVD prevention. 3,28,29 The advanced multimodality imaging approach of RURAL goes beyond traditional risk factor screening, providing a nuanced understanding of the multifaceted factors contributing to health inequalities. By leveraging cutting-edge technology and a range of scans, the RURAL study can effectively discern and address the complex interactions shaping health outcomes in rural communities, surpassing the limitations of conventional public health approaches.…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixth, participation in the GWTG-HF registry is voluntary and may not be representative of rural or urban hospitals. For example, rural hospitals in GWTG-HF tended to be larger than most rural US hospitals, and comorbidity burden among patients at rural GWTG-HF hospitals was similar to those at urban hospitals, which is different from some prior analyses of rural-urban disparities . Although prior studies have supported generalizability to US practice, quality of care and outcomes in hospitals participating in GWTG-HF may not reflect care delivered at all rural or urban hospitals .…”
Section: Discussionmentioning
confidence: 60%
“…Individuals living in rural areas of the US are at 19% higher risk of developing HF and experience higher rates of HF morbidity than their urban counterparts. 4 Our findings in combination with the disproportionate burden of HF in rural communities suggest rurality is an important factor to consider in clinical trial design.…”
mentioning
confidence: 77%